2015
DOI: 10.1159/000442237
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Thyroid Carcinoma: Disease Response Evaluation Using American Thyroid Association Risk Assessment Guidelines

Abstract: Objective: To evaluate the overall and progression-free survival for follicular thyroid carcinoma (FTC) based on the American Thyroid Association (ATA) staging system for recurrence risk assessment and the TNM staging system. Methods: A clinical review of FTC patients between 1995 and 2014 was conducted at a single center. The data was classified using the TNM staging system into low, intermediate, and high risk of recurrence as per the ATA risk assessment. Results: Over the course of 19 years, 114 (11.9%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We have also reported a similar trend for follicular thyroid cancer at our center. 6 The follicular variant of PTC did significantly better in terms of overall and disease-free survival compared with the classical variant. We did not have a large enough sample of the other variants to make a reliable comparison.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have also reported a similar trend for follicular thyroid cancer at our center. 6 The follicular variant of PTC did significantly better in terms of overall and disease-free survival compared with the classical variant. We did not have a large enough sample of the other variants to make a reliable comparison.…”
Section: Discussionmentioning
confidence: 91%
“…This is contrary to what we reported in follicular carcinoma thyroid, where age did not have a significant effect on the overall survival. 6 Over the recent years, we have been discharging low-risk patients from active follow-up if the initial 5 years show no biochemical or structural evidence of disease. This is in keeping with Garas et al 13 who after review of literature concluded that low-risk patients younger than 45 years of age with stage I disease show no survival benefit from lifelong follow-up after primary treatment and can be safely discharged to primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Distant metastasis at the time of initial presentation has a significant prognostic implication as the 10-year survival rate falls significantly to 50%. Factors including age, gender and distant metastasis are associated with survival outcomes in patients with WDTC ( 12 , 14 , 15 ). Metastasis to organs other than the bones and the lungs is not well understood and usually missed in clinical settings because of the rarity of such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the overall survival of our DTC population have already been published [4,5]. In the present study, although 18 F-FDG PET/CT played an instrumental role in detecting sites of disease in RRD, there was no clear-cut prediction of the development of RRD using the TNM staging or ATA risk assessment systems.…”
Section: Discussionmentioning
confidence: 62%